The writer’s pragmatic aims attainment in Doris Lessing’s To Room Nineteen: A cognitive linguistics view - Bystrov Yakiv; Sabadash Diana (Topics in Linguistics, 2019)
This paper presents an inquiry into the cognitive-pragmatic specifics of To Room Nineteen by Doris Lessing. Its major goal is to investigate the cognitive means that enable the fulfilment of the writer’s pragmatic aims in the process of literary communication. The research reveals the writer’s aims of raising the problem of women in a patriarchal society and of intensifying manipulative influence upon the reader, which were achieved via the implicit concept of NEUROSIS and the CONTAINER concept used to metaphorically interpret the described events. The investigation proved that the concept of NEUROSIS intensifies psychological manipulation of the reader, ensuring the reader’s engagement in message creation, preserving the reader’s trust regardless of the transference of inaccurate information, etc. It participates in the reader’s neural simulation through nomination of somatisms, retrieval of memories from previous painful experiences, the activation of the “mirroring” phenomenon, etc. Metaphoric modelling provides a psychological manipulation of the reader’s perception through shading and highlighting of the appropriate facets, creating proper associations and establishing specific images. It implements activation of the neural activity, creating imaginative simulation of the reader’s body in action and involving personal cognitive experiences.